Learned Helplessness, Discouraged Workers, and Multiple Unemployment Equilibria in a Search Model - Roger Bjørnstad (Statistics Norway, Research Department, 2001)
Unemployment varies strongly between countries with comparable economic structure. Some economists have tried to explain these differences with institutional differences in the labour market. Instead, this paper focuses on a model with multiple equilibria so that the same socioeconomic structure can give rise to different levels of unemployment. Unemployed workers' search efficiency are modelled within an equilibrium search model and lay behind these results. In the model learned helplessness causes a pro-cyclical behavior of the aggregate search efficiency, also known as the discouraged worker effect. The model can distinguish between locally stable and unstable labour market equilibria. The analysis shows that if a shock in an antecedent variable brings unemployment above the unstable equilibrium, the economy will eventually stabilize in a state with an even higher level of unemployment. However, a shock that brings the variable back at its initial level will not be enough to bring unemployment back at the lower equilibrium. Hence, the model also offers an explanation of why unemployment seems to move more easily up than down.
Keywords: J64; E24; 330; Learned helplessness; discouraged workers; multiple unemployment equilibria; search effectiveness; long term unemployment